The A REVIEW ON THE HOSPITALITY INDUSTRY - Jitin Sharma , Ashish Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this review, we need to show how DoubleTree by Hilton cooperates with its potential objective market and survey its utilization of innovation to speak with that market bunch. This study will research DoubleTree by Hilton's assets, as well as the organization's image character, its objective market portion, and the advances it utilizations to communicate with that gathering. As one of the best Starwood brands, the Double Tree by Hilton has had the option to separate itself in a cutthroat market by being perceived for its labor and products. Twofold Tree has had the option to hold a significant number of their clients returning in view of their prizes program